Bioactivity and pH of Nano-White MTA Versus NeoMTA(TM) Plus® and MTA Angelus® as Root Repair Materials: An “In Vitro” Study - ELKHASHAB, Rana; MAHRAN, Abeer; BADR, Mahmoud; ABU-SEIDA, Ashraf (International Arab Journal of Dentistry (IAJD), 2023)
Objective: This study compared the bioactivity and pH of Nano-white mineral trioxide aggregate (NWMTA), Neo-mineral trioxide aggregate plus (NeoMTA Plus), and Mineral trioxide aggregate angelus (MTA-A) as root repair materials. Methods: A total of 60 discs made from the three materials (20 discs each) were prepared accord ing to the manufacturer’s instructions. These discs were packed into plastic molds and allowed to set before testing. For bioactivity study, ten discs of each material were immersed in Hanks’ Balanced Salt Solution (HBSS) for 28 days, and analyzed with scanning electron microscope with energy dispersive X-ray (SEM/EDX). Ten discs of each material were used to assess the pH chang es by the pH meter at 3 h, 24 h, 72 h, and 168 h. All data were statistically analyzed. Results: After 28 days of immersing in HBSS, the crystals of Nano WMTA, NeoMTA Plus and MTA were covered with calcium phosphate precipitates with no statistically significant difference (P=0.908). The three tested materials induced alkalization of the deionized water after 3 h of immersion and started to decrease at 3 days continuing until the last test at 7 days. Conclusion: The Nano WMTA, NeoMTA Plus and MTA have similar bioactivity and strong alkalizing activity. Keywords: Apatite-forming ability, MTA angelus, Nano-White MTA, Neo-MTA plus, Root perforations